IMPLIKASI GENDER SEBAGAI MODERAtING vARIABLE DALAM KAItAN ANtAR IKLIM ORGANISASI, KEPuASAN KERjA , DAN KINERjA KARyAwAN PADA PERuSAhAAN DAERAh AIR MINuM tIRtA MANGutAMA KABuPAtEN BADuNG - I Made Purba Astakoni (Forum Manajemen STIMI Handayani Denpasar, 2014)
The success of the empowerment of human resources within anorganization is realized by the performance of its employees. Employees are animportant resource for the organization, because it has the talent, energy, andcreativity that is needed by the organization, not to mention the Regional WaterCompany (PDAM) Tirta Mangutama Badung regency. In this study, the objectivesof this study were: (1) To determine the effect of organizational climate on jobsatisfaction, (2) To determine the effect of organizational climate on employeeperformance, (3) To determine the effect of job satisfaction on employeeperformance, (4) To determine the effect of gender in moderating the relationshipbetween organizational climate, job satisfaction on employee performance.In getting the answers to the above research objectives in the census questionnairedistributed to 160 employees as respondents. Collected data were analyzed with theStructural Equation Model (SEM). In the first SEM method to evaluate the normalityof the data, confirmatory factor analysis (CFA) and then analyzes the influence of theSEM. Full results of the initial model showed that the model is not good so the modelneeds to be modified in order to obtain a model that approached Goodness of Fit.Results of this study indicate that the three hypotheses raised showed a significantpositive effect, namely: Effect of Organizational Climate (X1) of the EmployeeSatisfaction (Y1), Effect of Organizational Climate (X1) of the Employee Performance(Y2), Influence of Employee Satisfaction (Y1) the Employee Performance (Y2). Thereis the influence of Organizational Climate (X1), Employee Satisfaction (Y1) of theEmployee Performance (Y2). Employee Performance means variation of 79.90% canbe explained by the Organizational Climate and Job Satisfaction. There is also theinfluence of Employee Satisfaction (Y1), the Employee Performance (Y2). EmployeePerformance means variation of 27.90% influenced by the Employee Satisfaction. Fromthe results of the model turns moderating Gender male debilitating relationship betweenvariables Organizational Climate, Job Satisfaction and Employee Performance,Gender Women are not given effect to the models linkage raised in this study.